Association Between Hospital-Documented Atrial Fibrillation and Central Retinal Artery Occlusion. Issue 4 (2nd February 2023) - Lusk, Jay B.; Song, Ailin; Unnithan, Shakthi; Al-Khalidi, Hussein R.; Delic, Alen; de Havenon, Adam; Biousse, Valérie; Schrag, Matthew; Poli, Sven; Piccini, Jonathan P.; Xian, Ying; O'Brien, Emily C.; et al.
Abstract : Background: Carotid stenosis is thought to be the primary risk factor for central retinal artery occlusion (CRAO); however, it is not known whether atrial fibrillation (AF)—a cardiac arrhythmia that underlies over 25% of cerebral ischemic strokes—predisposes patients to CRAO. Methods: A retrospective, observational, cohort study was performed using data from the State Inpatient Databases and State Emergency Department Databases from New York (2006–2015), California (2003–2011), and Florida (2005–2015) to determine the association between AF and CRAO. The primary exposure was hospital-documented AF. The primary end point was hospital-documented CRAO, defined as having an International Classification of Diseases, Ninth Revision, Clinical Modification, code 362.31 in the primary diagnosis position. Cause-specific hazard models were used to model CRAO-free survival among patients according to hospital-documented AF status. Results: Of 39 834 885 patients included in the study, 2 723 842 (median age, 72.7 years; 48.5% women) had AF documented during the exposure window. The median follow-up duration was 6 years and 1 month. Patients with AF were older, more likely to be of non-Hispanic White race/ethnicity, and had a higher burden of cardiovascular comorbidities compared with patients without AF. The cumulative incidence of CRAO determined prospectively after exclusions was 8.69 per 100 000 at risk in those with AF and 2.39 per 100 000 at risk in those without AF over the study period. Before adjustment, AF was associated with higher risk of CRAO (hazard ratio, 2.55 [95% CI, 2.15–3.03]). However, after adjustment for demographics, state, and cardiovascular comorbidities, there was an inverse association between AF and risk of CRAO (adjusted hazard ratio, 0.72 [95% CI, 0.60–0.87]). These findings were robust in our prespecified sensitivity analyses. By contrast, positive control outcomes of embolic and ischemic stroke showed an expected strong relationship between AF and risk of stroke. Conclusions: We found an inverse association between AF and CRAO in a large, representative study of hospitalized patients; however, this cohort did not ascertain AF or CRAO occurring outside of hospital or emergency department settings.